DEVELOPMENT OF CONSTITUTIVE MODEL FOR CONCRETE IN CIRCULAR TUBE COMPOSITE COLUMN USING STEEL CONFINEMENT - JANSEN SARAGIH (NIM 25005029), IVAN
In this thesis, constitutive model for concrete column using steel tube as the confinement is presented, aiming to describe confinement effect of steel tube which contributes for axial capacity of concrete filled steel tubes ( CFST ) column. This study is using plasticity approach incorporated to a Four-Parameter Hsieh-Ting-Chen failure criteria under triaxial compression which lays on axisymmetric elements. Analysis contains three phases those are elastic, plastic and failure phase. During plastic loading, modification of Hsieh-Ting-Chen failure criteria as yield criteria for each subsequent loading surfaec is used. A Drucker-Prager criterion for Plastic Potensial function is selected for nonassociated plastic flow in this model, which represents the plastic dilatancy (volumetric expansion) that possess different slopes during plastic loading. The model’s performance is evaluated against experimental results and it is found that both have acceptanced similarity although some still rather large axial capacity deviation. Sensitivity analysis is implied to counter these deviations by modifying Drucker-Prager plastic potensial which has better results for the modification.